Analisis Strategi Bauran Pemasaran pada Properti Syariah studi kasus di Raudhoh Residence Bogor - Aripin, Siti Aulia Nur (Kasaba, 2021)
Basic human needs other than clothing and food are boards. As a basic human need, housing is a requirement to obtain welfare and even become a benchmark of well-being. In this case, property with sharia concept began to be widely developed, it is necessary to analyze the marketing mix strategy carried out on sharia property whether it is in accordance with Islamic law or not. The marketing mix has elements including: Price, Product, Place, Promotion, People, Process, and Physical Evidence. In this study aims to find out the marketing mix strategy on Sharia Property in Raudhoh Residence, as well as to know the marketing mix strategy to increase market share in Raudhoh Residence and find out if the marketing strategy at Raudhoh Residence is in accordance with Islamic law. The research method used is descriptive qualitative method. This research data uses primary data obtained from respondents through interviews with marketing Raudhoh Residence a sharia property company, as well as secondary data obtained from brochures and data released by Raudhoh Residence. The result of this research is That Raudhoh Residence has fulfilled all elements of the marketing mix in every unit sales process so that the company can achieve the targets specified in its sales ranging from Products, Prices, Places, People, Processes, Promotions, and Physical Environment. Marketing Mix Strategy that can increase market share is quality products, strategic location, transaction process in accordance with Islamic law and promotion using social media.